Political Participation in America, 1967 - Verba, Sidney ([Verlag nicht ermittelbar], 1984)
The focus of this study is individual political participation, both at the local and national levels. Respondents were asked to describe the most important recent changes and problems within their communities, how they kept informed of community and national events (media sources), their opinions of and interactions with community organizations as well as local, state, and national governments and political leaders, the role of government in solving emerging social problems, preference for local, state, or federal action, and how they voted in the presidential elections of 1960 and 1964. Background information on respondents includes age, race, sex, education, religion, employment status (including occupation and industry), marital status, political orientation and activity, years of local residency, age of children in household, and family income.